Osteopontin is associated with disease severity and antiphospholipid syndrome in well characterised Swedish cases of SLE. Issue 1 (28th July 2017) - Wirestam, Lina; Frodlund, Martina; Enocsson, Helena; Skogh, Thomas; Wetterö, Jonas; Sjöwall, Christopher
Abstract : Objective: The variety of disease phenotypes among patients with SLE challenges the identification of new biomarkers reflecting disease activity and/or organ damage. Osteopontin (OPN) is an extracellular matrix protein with immunomodulating properties. Although raised levels have been reported, the pathogenic implications and clinical utility of OPN as a biomarker in SLE are far from clear. Thus, the aim of this study was to characterise OPN in SLE. Methods: Sera from 240 well-characterised adult SLE cases classified according to the American College of Rheumatology (ACR) and/or the Systemic Lupus International Collaborating Clinics (SLICC) criteria, and 240 population-based controls were immunoassayed for OPN. The SLE Disease Activity Index 2000 (SLEDAI-2K) was used to evaluate disease activity and the SLICC/ACR Damage Index (SDI) to detect damage accrual. Results: Serum OPN levels were in average raised fourfold in SLE cases compared with the controls (p<0.0001). OPN correlated with SLEDAI-2K, especially in patients with a disease duration of <12 months (r=0.666, p=0.028). OPN was highly associated with SDI (p<0.0001), especially in the renal (p<0.0001), cardiovascular (p<0.0001) and malignancy (p=0.012) domains. Finally, OPN associated with coherent antiphospholipid syndrome (APS; p=0.009), and both clinical and laboratory criteria of APS had significant positive impact on OPN levels. Conclusions: In this cross-sectional study, circulating OPN correlates with disease activity in recent-onset SLE, reflects global organ damage and associates with APS. Longitudinal studies to dissect whether serum OPN also precedes and predicts future organ damage are most warranted.